Combustible Material Content vs. Fire Properties of Electric Cables - Katarzyna Kaczorek-Chrobak; Jadwiga Fangrat (Energies, 2020)
The fire load of buildings is significantly increased by means of electric cables, usually creating a long combustible base for fire to spread and in this way decreasing the fire safety of buildings. The aim of the study was to evaluate a relationship between the construction of the cables and their fire properties, especially the mass loss influence on other fire properties of cables. Six cables of different core numbers were tested by means of the standard test method EN 50399. Additionally, thermogravimetric analysis and Attenuated Total Reflection—Fourier Transform Infrared analysis were performed on the separate outer sheath, bedding, and core insulations in order to determine the similarity of the materials’ chemical structures. It was found that: (1) the construction of the cable strongly influences the fire behavior due to the creation of a barrier for flame penetration and emission of combustion effluents though inside the closed agglomeration of non-combustible metallic cores (conductors), and the intumescent structures formed from aluminum trihydrate/zinc borate fillers and fire retardants in outer sheath material during the self-sustained combustion process after ignition of cables; (2) the inhomogeneous distribution of non-combustible inorganic fillers or different contents of fillers and flame retardants within the polymer fraction cause an unobvious fire behaviors of cables; and (3) the use of bedding in multicore cable construction results in lower values of combustion parameters (maximum average heat release rate, total heat release, maximum average smoke production rate, total smoke production), e.g., better fire properties of cables.